2021
DOI: 10.3389/fmicb.2021.656895
|View full text |Cite
|
Sign up to set email alerts
|

GABA Production by Human Intestinal Bacteroides spp.: Prevalence, Regulation, and Role in Acid Stress Tolerance

Abstract: The high neuroactive potential of metabolites produced by gut microbes has gained traction over the last few years, with metagenomic-based studies suggesting an important role of microbiota-derived γ-aminobutyric acid (GABA) in modulating mental health. Emerging evidence has revealed the presence of the glutamate decarboxylase (GAD)-encoding gene, a key enzyme to produce GABA, in the prominent human intestinal genus Bacteroides. Here, we investigated GABA production by Bacteroides in culture and metabolic assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 69 publications
2
93
0
Order By: Relevance
“…Recently, Bacteroides spp. have been confirmed as producers of GABA as a mechanism of stress tolerance in humans [ 43 ]. Furthermore, other bacteria taxa, which were altered in our experimental approach, such as Escherichia coli and lactic acid bacteria have been found to also produce neurotransmitters such as serotonin [ 44 ] and GABA [ 45 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bacteroides spp. have been confirmed as producers of GABA as a mechanism of stress tolerance in humans [ 43 ]. Furthermore, other bacteria taxa, which were altered in our experimental approach, such as Escherichia coli and lactic acid bacteria have been found to also produce neurotransmitters such as serotonin [ 44 ] and GABA [ 45 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of PLP and MSG at their specific concentrations was also essential in boosting GABA production. Besides some common factors, microbial strains, specifically selected for GABA synthesis, might require additional requirements and modifications, which would be unique to each strain of bacteria or fungi for achieving maximum yield of GABA [32][33][34][35][36][37].…”
Section: Manipulations Of Microbesmentioning
confidence: 99%
“…The GAD-system consists of at least four highly conserved genes encoding a GAD, a glutaminase, a glutamate/GABA antiporter, and a potassium channel with the high prevalence of the GAD-system among Bacteroides. Studies had shown glutamate and glutamine as precursors of GABA production and Bacteroides have an important role in the regulation of the GABAergic system in the human gut [45] . Alteration in bacterially derived GABA and/or GAD-system genes may account for mental health issues like depression [44,46] .…”
Section: Gaba and Gut Microbesmentioning
confidence: 99%